2012
DOI: 10.1371/journal.pone.0034892
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxyl (HNO) Stimulates Soluble Guanylyl Cyclase to Suppress Cardiomyocyte Hypertrophy and Superoxide Generation

Abstract: BackgroundNew therapeutic targets for cardiac hypertrophy, an independent risk factor for heart failure and death, are essential. HNO is a novel redox sibling of NO• attracting considerable attention for the treatment of cardiovascular disorders, eliciting cGMP-dependent vasodilatation yet cGMP-independent positive inotropy. The impact of HNO on cardiac hypertrophy (which is negatively regulated by cGMP) however has not been investigated.MethodsNeonatal rat cardiomyocytes were incubated with angiotensin II (An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…It has also been suggested that HNO may mediate, at least in part, some of the biological effects traditionally attributed to endogenous NO˙(2, 26). It is thus now apparent, however, that HNO offers considerable advantages in the treatment of cardiovascular disease (26,31,38,44).In addition to these aforementioned protective cardiovascular actions, the distinct pharmacology of HNO gives rise to a spectrum of unique properties that potentially position HNO-based pharmacotherapies even more favorably than their NO˙-based counterparts. HNO, in direct contrast to NO˙, resists scavenging by superoxide (30,36), is resistant to vascular tolerance development (23, 25), and enhances myocardial contractility (39, 40).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has also been suggested that HNO may mediate, at least in part, some of the biological effects traditionally attributed to endogenous NO˙(2, 26). It is thus now apparent, however, that HNO offers considerable advantages in the treatment of cardiovascular disease (26,31,38,44).In addition to these aforementioned protective cardiovascular actions, the distinct pharmacology of HNO gives rise to a spectrum of unique properties that potentially position HNO-based pharmacotherapies even more favorably than their NO˙-based counterparts. HNO, in direct contrast to NO˙, resists scavenging by superoxide (30,36), is resistant to vascular tolerance development (23, 25), and enhances myocardial contractility (39, 40).…”
mentioning
confidence: 99%
“…It has also been suggested that HNO may mediate, at least in part, some of the biological effects traditionally attributed to endogenous NO˙(2, 26). It is thus now apparent, however, that HNO offers considerable advantages in the treatment of cardiovascular disease (26,31,38,44).…”
mentioning
confidence: 99%
See 3 more Smart Citations